1992
DOI: 10.1002/bies.950141004
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of origins of DNA replication in eukaryotes

Abstract: Chromosomal origins of DNA replication in higher eukaryotes differ significantly from those of E. coli (oriC) and the tumor virus, SV40 (ori sequence). Initiation events appear to occur throughout broad zones rather than at specific origin sequences. Analysis of four chromosomal origin regions reveals that they share common modular sequence elements. These include DNA unwinding elements, pyrimidine tracts that may serve as strong DNA polymerase-primase start sites, scaffold associated regions, transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 58 publications
(30 reference statements)
0
45
0
Order By: Relevance
“…This region was shown to contain a strong promoter for the downstream transcription unit; a key feature ofthis promoter is the presence of a basic helix-loop-helix protein binding motif that was shown to bind in vitro to the USF/MLTF protein (23); interestingly, such motif also fits the binding consensus for the Myc/Max complex (24), whose function in regulating cell proliferation is suggested by several studies (25) [incidentally, the c-myc gene domain is amplified in HL-60 cells (26)]. An evolutionary conserved (A+T)-rich region (22) can be envisaged in the proximity of the origin, as is the case for well-defined replication origins of different organisms (27)(28)(29).…”
Section: ~-F )W Lmentioning
confidence: 81%
“…This region was shown to contain a strong promoter for the downstream transcription unit; a key feature ofthis promoter is the presence of a basic helix-loop-helix protein binding motif that was shown to bind in vitro to the USF/MLTF protein (23); interestingly, such motif also fits the binding consensus for the Myc/Max complex (24), whose function in regulating cell proliferation is suggested by several studies (25) [incidentally, the c-myc gene domain is amplified in HL-60 cells (26)]. An evolutionary conserved (A+T)-rich region (22) can be envisaged in the proximity of the origin, as is the case for well-defined replication origins of different organisms (27)(28)(29).…”
Section: ~-F )W Lmentioning
confidence: 81%
“…SC). These features may be important for the establishment of a preinitiation complex, since both DNA polymerase o-primase and HSSB, which play essential roles in the initiation of DNA replication in this system, bind preferentially to the single-stranded DNA containing pyrimidine-rich sequences (4,24 (Fig. 5A), suggesting the interaction of HSSB with the region.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analyses of prokaryotic and eukaryotic viral origins of replication have revealed that a prerequisite for initiation of replication is unwinding of double-stranded DNA (reviewed in references 10 and 11). Whereas the unwinding of DNA in prokaryotic and viral replication origins is dependent on sequence-specific binding of initiator proteins to the origin sequences and the unwound regions are restricted to the adjacent regions, there may be a mechanism in higher eukaryotes that can unwind DNA in a much extended region as proposed by Benbow and coworkers (7,28).…”
Section: Materiails and Methodsmentioning
confidence: 99%